2015
DOI: 10.1111/ipd.12167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sealing infected dentin with glass ionomer cement on the abundance and localization of MMP‐2, MMP‐8, and MMP‐9 in young permanent molars in vivo

Abstract: The sealing of infected carious dentin in young permanent molars reduced the expression of MMP-8, which is consistent with the initial remodeling process of the dentin matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
4
10
0
1
Order By: Relevance
“…45 Meanwhile, SDF showed the same action in less time with a high amount of fluoride and silver halt active carious lesions and provide antibacterial action. Our findings agree with another study, 41 which compared the remineralizing and antibacterial effect of SDF and propolis. It was found that SDF had superior antibacterial and remineralizing ability, which was attributed to the concentration of active ingredients in SDF that reach up to 38%, as opposed to propolis fluoride which only contains 10% active material.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…45 Meanwhile, SDF showed the same action in less time with a high amount of fluoride and silver halt active carious lesions and provide antibacterial action. Our findings agree with another study, 41 which compared the remineralizing and antibacterial effect of SDF and propolis. It was found that SDF had superior antibacterial and remineralizing ability, which was attributed to the concentration of active ingredients in SDF that reach up to 38%, as opposed to propolis fluoride which only contains 10% active material.…”
Section: Discussionsupporting
confidence: 93%
“…After 6 weeks the propolis group had increased mineral density of carious dentin mainly due to flavonoids present in it that can induce reparative dentin through upregulation of growth factors (TGF-β1) which interact with the extracellular matrix resulting in collagen formation. 41,42 Furthermore, flavonoids can inhibit microorganisms by denaturing proteins and nucleic acids. Hindering of bacteria will decrease demineralization and help in mineral precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study revealed that after SCT, dentin degradation might increase, due to MMP-8. Other authors described a lower expression of MMP-8 in visit 2 after SCT and sealing caries altered dentin [48], as well as a slight decrease of MMP-8 activity with "increasing depth of dentinal caries lesions" [47]. Tissue inhibitors of metalloproteinases, which were also considered within the present investigation, are known to control MMP activity, thus limiting dentin breakdown can be assumed [49,50].…”
Section: Discussionsupporting
confidence: 50%
“…The importance of good dentine sealing on inhibiting MMP activity has previously been addressed in the literature [ 44 , 45 ]. Low pH caused by the natural caries process (bacterial acids) or acid-etching can result in activation of the MMP enzymes.…”
Section: Discussionmentioning
confidence: 99%